Optimization Utilization of Water Resourcesdam Batutegi Usingmethod of Linear Program - Aprizal Aprizal; Hery Fitriyansyah (Bandar Lampung University (UBL), 2013)
Water is the source of life and take on an important role in supporting human activities. Form of the problems faced in the utilization of water resources management in general is a problem right way so that at the optimum can result from existing resources. Efforts should be made to overcome these problems by taking into account the constraints faced, the negative impacts and completion is expected to be effective and efficient.Among the various alternatives, the research to optimize the utilization of the water dam Batutegi an option. Linear program is one form of optimization techniques. The objective function is to maximize the amount of water that can be supplied for irrigation. The problem is the availability of water in the dam Batutegi. Completion of this optimization problem using QM For Windows software.Efficiency optimization results are outflows of 2:05 m3/sec in the first growing season, 1:19 m3/sec in the second growing season and the addition of irrigated area of 1,100 ha in the first growing season, 512 ha in the second growing season.